THE EFFECT OF JIGSAW TEACHING TECNIQUE ON STUDENTS’ ABILITY IN WRITING A DESCRIPTIVE TEXT AT ELEVENTH GRADE STUDENTS OF SMK GKPI 2 PEMATANGSIANTAR - Febriana Monika Napitupulu; Sanggam Siahaan; Bloner sinurat (RADJA PUBLIKA, 2025)
This study aims to investigate the effect of the Jigsaw teaching technique on students’ ability in writing descriptive text at the eleventh grade students of SMK GKPI 2 Pematangsiantar. This research used a quantitative method with a quasi-experimental design. The population of this study consisted of 60 students, and the sample was divided into two groups: the experimental class (XI-1) and the control class (XI-2), each consisting of 30 students. The experimental class was taught using the Jigsaw teaching technique, while the control class was taught using a conventional teaching method. The instrument used to collect the data was a writing test in the form of pre-test and post-test. The results of the study showed that the students’ writing ability improved after the implementation of the Jigsaw technique. The mean score of the experimental class increased from 54.00 in the pre-test to 80.46 in the post-test, while the control class improved from 53.21 to 71.21. The result of the t-test analysis showed that the t-observed value (2.44) was higher than the t-table value (2.00) at the significance level of 0.05. This indicates that the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. Based on the findings, it can be concluded that the Jigsaw teaching technique has a significant effect on students’ ability in writing descriptive text. Therefore, the Jigsaw technique is recommended as an effective teaching strategy to improve students’ writing skills.